Video-assisted minimally invasive diaphragmatic plication: feasibility of a recognized procedure through an uncharacteristic hybrid approach - LAÇİN, TUNÇ (SPRINGER, 2017)
Background Diaphragmatic plication is an approved surgical procedure for treatment of symptomatic diaphragmatic paralysis and eventration. We aim to define our minimally invasive technique of plication and objectively assess our surgical outcomes of the largest series reported in the literature so far, using pulmonary function tests. Methods Symptomatic patients whom were planned to undergo plication using video-assisted mini-thoracotomy between December 2009 and December 2015 were the cohort of this retrospective study. Single camera port and a utility incision (3-4 cm) were used for access. Data of patient demographics with preoperative and postoperative spirometric results were collected for statistical comparison. Results Procedure (30 left, 7 right) was completed in 37 (27 male, 10 female) patients. One patient was excluded because of insufficient objective postoperative comparison criteria due to previous permanent tracheostomy. Mean length of surgery was 48.8 +/- 19.7 (range: 30-70) min. Postoperative overall morbidity was 8.3 %, with no mortality. The mean length of hospital stay was 3.1 +/- 1.7 days. All patients except one (97.3 %) were asymptomatic on discharge and on follow-ups. Significant improvement in measurements of forced expiratory volume in 1st second was observed on postoperative measurements (P < 0.001), with a mean overall increase of 13 % in whole cohort. No recurrence was detected throughout a mean follow-up of 19 months. Conclusions Diaphragmatic plication via video-assisted mini-thoracotomy is an effective and curative surgical procedure which can be performed successfully with low morbidity rates. As it combines the rapidity and economical benefits of open thoracotomy with the advantages of video thoracoscopic procedures such as fast recovery and short postoperative hospital stay, it can be preferred as a safe and effective alternative hybrid method compared to standard open or closed techniques, for symptomatic patients with non-functional hemidiaphragm.
Keywords: Diaphragm; Eventration; Minimally invasive surgery; Plication; Video-assisted thoracoscopic surgery (VATS); THORACOSCOPIC PLICATION; PULMONARY-FUNCTION; EVENTRATION; PARALYSIS; TERM; ADULTS